THE ANALISYS OF RAILWAY MULTI MOTORS ELECTRICAL DRIVE DYNAMIC - V. I. Khilmon; O. F. Opeiko; D. S. Odnolko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The importance of multi motors electrical traction drive dynamic analysis is denoted by its large application in electrical driving railway vehicles. In this paper an analysis is presented for two inducton motors traction drive with frequency inverter, vector control, and speed sensors of each electrical drive. The goal of this work is the analysis of two induction motors electrical drive, taking into account parametric perturbations and also a limited moment of wheel-rail adhesion, by laboratory study and simulation. Because of difference between motor’s parameters, it is necessary for parallel work to select motors with identical resistances and inductive winding. For this purpose the parametric identification method was used for each electrical drive, and also for two parallel motors. The result of identification was used in control setting.The  slippage  of  the  traction  drives  is  difficult  to  reproduce  in  laboratory;  therefore a mathematical modeling and simulation of mechanical part with a traction force restriction, specific for railway transport, were carried out. The suggested simulation is built with account of elastic deformations in kinetic chain, transforming traction force. The model permits to study a dynamic system in various circumstances.The results of laboratory investigations and simulation of dynamic regimes for two motor electrical drives are presented in this article. The results of analysis show, that a minimal difference between any parameters of two motors, parallel connected to convertor, is important for the slippage stability.